MADUREZ TERMICA DE LAS SECUENCIAS CENOZOICAS DEL SUR DE CHILE - María Eugenia Cisternas; Ursula Kelm; Marcos Zentilli (Publicación Electrónica de la Asociación Paleontológica Argentina, 2015)
The lower (Oligo-Miocene) continental section of the Cenozoic sequence in the South of Chile (Regions IX and X) carries coal seams, while the upper marine (Mid Miocene) has potential for hydrocarbon generation. Due to the potential economic importance of the Cenozoic strata, the thermal maturity has been investigated by comparison of inorganic (clays, zeolites) and organic (vitrinite reflectance) diagenetic indicators. The diagenetic level of the clays, zeolites and organic matter in samples from drill holes in the Temuco, Valdivia and Osomo provinces indicate that both the lower continental and upper marine sequences are immature. The catagenesis zone has not been reached in any of the drill holes sampled. lt seems improbable that any significant quantity of crude has been generated and only sub-bituminous quality coal is expected. The block-controlled post-Miocene tectonic framework, that defines the actual morphostructural landscape, makes areas with thicker overbunden (i.e. central Valley) a more prospective ground for studies. There deeper burying may have produced higher thermal maturity; therefore favoring hydrocarbon generation and increasing the coal maturity.